2021
DOI: 10.1111/ajag.12975
|View full text |Cite
|
Sign up to set email alerts
|

Medication‐related hospital admissions in aged care residents

Abstract: Objective To determine the prevalence of medication‐related hospitalisations preceded by potentially suboptimal processes of care in aged care residents. Method We conducted a retrospective analysis of administrative claims data from the Australian Government Department of Veterans’ Affairs (DVA). We identified all hospital admissions for aged care residents between 1 July 2014 and 30 June 2019. The proportion of hospital admissions preceded by potentially suboptimal medication‐related processes of care was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recent studies have also observed higher preventability: 60.9% ( Li et al, 2021 ) 42.9% ( Dechanont et al, 2021 ), 53.5% ( Maříková et al, 2021 ), 46% ( Kalisch Ellett et al, 2021 ) 47% ( Lombardi et al, 2020 ), 76.4% ( Cabre et al, 2018 ) 69% ( Giardina et al, 2018 ). However, most of them were limited to older patients, in whom the preventability is higher than in the general population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies have also observed higher preventability: 60.9% ( Li et al, 2021 ) 42.9% ( Dechanont et al, 2021 ), 53.5% ( Maříková et al, 2021 ), 46% ( Kalisch Ellett et al, 2021 ) 47% ( Lombardi et al, 2020 ), 76.4% ( Cabre et al, 2018 ) 69% ( Giardina et al, 2018 ). However, most of them were limited to older patients, in whom the preventability is higher than in the general population.…”
Section: Discussionmentioning
confidence: 93%
“…In a study in Belgium ( Somers et al, 2010 ), the most common symptom associated with drug therapy failures was dyspnea. A study from Australia ( Kalisch Ellett et al, 2021 ) identified that chronic heart failure and osteoporosis were most frequently associated with potentially suboptimal medication-related processes of care related to the underuse of medications. However, there are not many studies that focus not only on DRAs related to treatment safety but also on DRAs related to treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Around one in five hospitalizations among older Australians are medicines‐related 9 . Similarly, a previous study in Australia reported that 46% of the hospitalizations among older residents were due to potentially suboptimal use of medicines 11 . In addition, many aged care residents were on fall‐risk drugs and visited hospital with fractures.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, a previous study in Australia reported that 46% of the hospitalizations among older residents were due to potentially suboptimal use of medicines. 11 In addition, many aged care residents were on fall‐risk drugs and visited hospital with fractures. Discontinuation or dose reduction in fall‐risk drugs significantly reduces the occurrence of falls in older people.…”
Section: Introductionmentioning
confidence: 99%